MITHT DURING THE GREAT PATRIOTIC WAR (1941- 1945). THE BEGINNING OF THE WAR - G. N. Yakovleva; B. F. Bogatikov (Тонкие химические технологии)
The article is dedicated to the memorable tragic date - to the 75th anniversary of the beginning of the Great Patriotic War of 1941-1945 and to the activity of the Lomonosov Moscow Institute of Fine Chemical Technology in 1941-1942: mobilization, evacuation, renewal of the educational and scientific activity in the conditions of the martial law.